2023
DOI: 10.3389/fonc.2023.1036455
|View full text |Cite
|
Sign up to set email alerts
|

High risk-myelodysplastic syndrome following CAR T-cell therapy in a patient with relapsed diffuse large B cell lymphoma: A case report and literature review

Abstract: BackgroundChimeric antigen receptor (CAR) T-cell therapy represents the most advanced immunotherapy against relapsed/refractory B cell malignancies. While cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome are distinctive, known CAR T-cell acute adverse events, hematological toxicity has been increasingly reported. Cytopenia following CAR T-cell treatment is attributed in most cases to lymphodepletion regimens, bridging chemotherapy, or radiotherapy. However, when cytopenia be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“… 47 Accorsi Buttini et al also reported that one patient with R/R DLBCL based on sustained CSF3R and CEBPA mutations developed secondary MDS and acquired a new RUNX1 mutation after CAR‐T‐cell therapy. 48 These two cases suggest that CAR‐T‐cell treatment is similar to a double hit to promote development of MDS for those who already have clonal haematopoiesis prior to CAR‐T‐cell therapy. Conversely, Zhao et al reported an incidence of therapy‐related myeloid neoplasms after CAR‐T‐cell therapy of 3.2%, comparable to that in patients who received chemotherapy or HSCT; hence, they deemed that CAR‐T‐cell infusion did not significantly increase the risk of therapy‐related myeloid neoplasms according to the current data for incidence.…”
Section: Mechanisms Of Prolonged Haematologic Toxicitymentioning
confidence: 97%
See 2 more Smart Citations
“… 47 Accorsi Buttini et al also reported that one patient with R/R DLBCL based on sustained CSF3R and CEBPA mutations developed secondary MDS and acquired a new RUNX1 mutation after CAR‐T‐cell therapy. 48 These two cases suggest that CAR‐T‐cell treatment is similar to a double hit to promote development of MDS for those who already have clonal haematopoiesis prior to CAR‐T‐cell therapy. Conversely, Zhao et al reported an incidence of therapy‐related myeloid neoplasms after CAR‐T‐cell therapy of 3.2%, comparable to that in patients who received chemotherapy or HSCT; hence, they deemed that CAR‐T‐cell infusion did not significantly increase the risk of therapy‐related myeloid neoplasms according to the current data for incidence.…”
Section: Mechanisms Of Prolonged Haematologic Toxicitymentioning
confidence: 97%
“…47 Accorsi Buttini et al also reported that one patient with R/R DLBCL based on sustained CSF3R and CEBPA mutations developed secondary MDS and acquired a new RUNX1 mutation after CAR-T-cell therapy. 48 These two cases suggest that TA B L E 1 Factors related to prolonged haematologic toxicity.…”
Section: Clonal Haematopoiesis and Secondary Myelodysplastic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…However, the downregulation of inhibitory molecules can lead to uncontrolled T-cell proliferation or increased risk of autoimmunity, and the use of exogenous cytokines can lead to the development of serious adverse effects. Thus, in late January 2024, the FDA recommended including new “black box” warnings for CAR-T-cell therapy after reviewing clinical trial reports describing the occurrence of mature CAR-positive T-cell malignancies following CAR-T-cell immunotherapy [ 179 , 180 ].…”
Section: The Cancer Immunotherapy Strategiesmentioning
confidence: 99%
“…42 Other studies have reported myeloid malignancies development in LBCL patients undergoing anti-CD19 CAR-T cell treatments. [43][44] The precise mechanism behind the increased risk of tMN has to be elucidated and remains subject to speculation. It remains unclear whether the particular immune dysregulation in patients after CAR-T plays an important role or whether the occurrence of tMN is simply the consequence of genetic damage induced by the precedent lines of therapy in these mostly heavily pretreated patients.…”
Section: Clonal Hematopoiesis and Car-t Cell Therapymentioning
confidence: 99%